2010
DOI: 10.1007/978-1-60761-938-3_6
|View full text |Cite
|
Sign up to set email alerts
|

The Blood-Nerve Barrier: Structure and Functional Significance

Abstract: The blood-nerve barrier (BNB) defines the physiological space within which the axons, Schwann cells, and other associated cells of a peripheral nerve function. The BNB consists of the endoneurial microvessels within the nerve fascicle and the investing perineurium. The restricted permeability of these two barriers protects the endoneurial microenvironment from drastic concentration changes in the vascular and other extracellular spaces. It is postulated that endoneurial homeostatic mechanisms regulate the mili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
109
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 73 publications
1
109
0
Order By: Relevance
“…Approximately 40 % of sensory neurons diminish within 2 months after peripheral axotomy. Similar phenomena are also observed clinically following peripheral nerve injury [11]. Swelling occurs following nerve damage in the proximal segment, while the distal stump undergoes degeneration; however, regenerating axons can be detected as early as 24 h following the injury.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Approximately 40 % of sensory neurons diminish within 2 months after peripheral axotomy. Similar phenomena are also observed clinically following peripheral nerve injury [11]. Swelling occurs following nerve damage in the proximal segment, while the distal stump undergoes degeneration; however, regenerating axons can be detected as early as 24 h following the injury.…”
Section: Introductionmentioning
confidence: 61%
“…The recorded high rate of neuronal death in our experimental groups is undoubtedly associated with serious traumatization of the sciatic nerve and the two suture lines create a serious obstacle for the regenerating axons [11]; however, the transplantation of the hADSCs considerably contributes to the neuronal survival of the L5 spinal ganglion after the autonerve grafting. We have found that it is only in the group with the cell stimulation, and exclusively in the neurons of a large diameter, that doubling of nucleoli Red fluorescence corresponds to the positive reaction with caspase-9.…”
Section: Discussionmentioning
confidence: 99%
“…At the early stage of inflammation, the release of chemokines and increase in the permeability of blood–nerve barrier were accomplished simultaneously 30. Blood‐borne macrophages attracted from surrounding circumstance would traverse these vessels along the gradient and the majority of active macrophages was hematogenous.…”
Section: Discussionmentioning
confidence: 99%
“…Successful regeneration is a consequence of well orchestrated interactions between axotomized neurons and non-neuronal cells, especially Schwann cells and macrophages. These interactions are triggered upon injury and initiate a cascade of cellular and molecular reactions including local damage of the blood-nerve-barrier (Weerasuriya and Mizisin 2011;Gray et al 2007;Bouldin et al 1991), degeneration of the distal part of severed axons (Tsao et al 1999;Perry et al 1990;Lubinska 1977), dedifferentiation and proliferation of Schwann cells (LeBlanc and Poduslo 1990), recruitment of hematogenous macrophages LeBlanc and Poduslo 1990), reorganization of the endoneurial extracellular matrix (ECM) (Gantus et al 2006;Tona et al 1993), as well as the release of cytokines, neurotrophins and growth factors (Gordon 2009;Ruohonen et al 2005;Shamash et al 2002). In this way, an axon growthpermissive microenvironment is formed predominantly by non-neuronal adjacent cells, which significantly enhances the intrinsic growth potential of injured peripheral neurons.…”
Section: Introductionmentioning
confidence: 99%